Chemical composition, antibacterial, antifungal and antioxidant activities of Taxus baccata essential oil from Algeria - Khaoula Benlembarek; Takia Lograd; Messaoud Ramdani; Gilles figueredo; Pierre Chalard (Society for Indonesian Biodiversity, 2021)
Abstract. Benlembarek K, Lograda T, Ramdani M, Figueredo G, Chalard P. 2021. Chemical composition, antibacterial, antifungal and antioxidant activities of Taxus baccata essential oil from Algeria. Biodiversitas 22: 5475-5483. This work aims to study the chemical composition, the antibacterial, antifungal and antioxidant activities of Taxus baccata essential oil of Algeria. The essential oil was obtained by hydro distillation; its chemical composition was determined by GC and GC-MS analysis. The antibacterial and antifungal activities are evaluated by the disk diffusion method against three-gram negative bacteria, four-gram positive bacteria and four phytopathogenic fungi. The evaluation of antioxidant activity is carried out by the DPPH scavenging method. Twenty-seven compounds have been identified in the essential oil, where the major product was undecanone-2, followed by nonanone-2, tridecanone-2, decanone-2 and the methyl dehydroabietic. The T. baccata essential oil showed moderate antibacterial and antifungal activities against the strains tested, with the exception of E. faecalis, MRSA and Fusarium graminum, which have shown significant resistance. T. baccata essential oil has a moderate antioxidant activity.